Determinants of undergoing thyroid cancer screening in Korean women: a cross-sectional analysis from the K-Stori 2016. Issue 4 (3rd April 2019) - Cho, Ha Na; Choi, Eunji; Seo, Da Hea; Park, Boyoung; Park, Sohee; Cho, Juhee; Kim, Sue; Park, Yeong-Ran; Rhee, Yumie; Choi, Kui Son
Abstract : Objectives: Thyroid cancer is the most common cancer among Korean women. Studies suggest that the incidence of thyroid cancer might be associated with overdiagnosis resulting from thyroid cancer screening. The objective of this study was to identify the determinants of participation in thyroid cancer screening in Korean women. Methods: Data were obtained from the 2016 Korean Study of Women's Health-Related Issues, a nationwide cross-sectional survey of women according to the reproductive life cycle. A total of 8697 cancer-free women of ages between 20 and 79 years were included for analysis. Multivariable logistic regression analysis was applied to analyse factors associated with adherence to thyroid cancer screening based on Andersen's health behavioural model. Results: Over the last 2 years, the rate of thyroid cancer screening was 39.2%. In multivariable models, older age, higher household income, high school education level and higher perceived risk of cancer were positively associated with thyroid cancer screening participation. Moreover, women who underwent cervical cancer screening (adjusted OR [aOR] 3.67; 95% CI 2.90 to 4.64) and breast cancer screening (aOR 10.91; 95% CI 8.41 to 14.14) had higher odds of attending thyroid cancer screening than women who did not attend cancer screening. Conclusions: These findings highlight the need to increase awareness of different recommendations on screening for various cancers to improve cost-effectiveness and to prevent unnecessary treatments.